Implementasi Model Pelayanan Sosial Penanggulangan Masalah Trafficking - Kissumi Diyanayati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
The model of social service on trafficking prevention is implemented esentially by stakeholders covering prevention, undertaking, and rehabilitation of the victims problems. The model is implemented in two locations, Medan Municipality and Pakpak Bharat Regency. The model is implemented in six months, through seeking local permision, socialization of the model, activity coordination with local institutions related to this case to shape the same perception, special task action plan, implementation of the model, monitoring, and evaluation. The implementation is working as expected, manifested through establising Local Anti-trafficking Disemination Team (D2AMT) in each location that have been succesfully preventing against trafficking problem through socialization in several schools, mosques and churches youth, and local public figures. Due to involving many aspects, coordination among stakeholders on trafficking prevention is needed, sort of poverty, education, human resources, and criminal conducts.